THE ROLE OF ARTIFICIAL INTELLIGENCE TO DEVELOP FINANCIAL TECHNOLOGY AT THE BANKS (IRAQ, CASE STUDY) - Assist. Prof. Dr. Azhar Shamran Jabur; Prof. Dr. Ahmed Abdullah Salman (Scholars Digest Publishing, 2024)
The world today is witnessing a lot of progress and advancement in many sectors and fields, through using electronic programs to keep up with advanced countries, where technology and artificial intelligence are really important for businesses environment nowadays. Financial institutions also use the diversification factor in strategies for using advanced banking services such as ATMs, internet and digital screens to achieve customer satisfaction and keep up with growth and development in the business role financial institutions especially banks in developed countries. The objective of study is aiming to study and analyze the role of artificial intelligence and advanced technologies in providing banking services to financial institutions, which are used to provide banking services to customers using modern and advanced methods of access their satisfaction at the lowest cost and for the shortest time. Researchers used artificial intelligence and financial technology measurements to analyze financial institutions, especially banks, and found advanced and sophisticated control systems as well as providers increases the quality and efficiency of banking operations.by increasing the level of competition, reducing costs, and reducing the level of risk. The researchers recommend the necessity of using more advanced and sophisticated programs for artificial intelligence and technology in the provision of banking services in order to enhance the opportunities for growth, continuity, and survival in the work of banks, especially since the use of modern technology contributes to the innovation of new and modern methods and means in the provision of banking services to customers in order to achieve their satisfaction and gain more of them, as well as benefiting from the experiences of developed and advanced countries in the application of artificial intelligence programs and modern financial technology in order to deliver electronic financial services to all segments of society.